A Pilot Investigation of the Social Attention and Communication Surveillance (SACS) Tool for the Early Identification of Autism in Tianjin, China (SACS-C) - Barbaro, Josephine; Wang, Chongying; Wang, Jing; Liu, Gongshu; Liang, Ying; Wang, Ji; Abdullahi, Ifrah; Dissanayake, Cheryl (Frontiers in Neurology, 2020)
Introduction: Autism spectrum disorder (ASD) comprises difficulties in social communication and restrictive and repetitive behaviours. Despite an increased global prevalence, little remains known about detection and diagnosis of ASD in mainland China. Our aim was to conduct a pilot investigation of Social Attention and Communication Surveillance in Tianjin, China (SACS-C) to identify ASD early by professionals, compared to the Checklist for Autism in Toddlers-23 (CHAT-23) completed by parents and professionals. Methods: A total of 10,514 children were monitored at the Tianjin Women and Children’s Health Centre (TWCHC) on the SACS-C at 12 - 24 months of age following a half-day training of 225 child health practitioners. Children deemed at “high likelihood” for ASD on either the SACS, CHAT-23, or both, were referred for developmental assessments at TWCHC. Results: A total of 87 children (0.8%) were identified at “high likelihood” on the SACS-C, of whom 57 were assessed for ASD (66%); 24 children were subsequently diagnosed with ASD (42.1%), and the remaining 33 (57.9%) were diagnosed with developmental and/or language delays. The SACS-C had a positive predictive value (PPV) of 42.1%, a negative predictive value (NPV) of 99.8%, and sensitivity and specificity of 53.3% and 99.7%, respectively. Only 21 children were identified at “high risk” for ASD on the CHAT-23 (.2%), with 14 children assessed for ASD (66%); nine were diagnosed with ASD (64.3%) and the remaining five children were diagnosed with developmental and/or language delays. The CHAT-23 had an overall PPV of 64.3%, NPV of 99.6%, sensitivity of 27.3%, and specificity of 99.9%. Conclusion: This was the first large-scale study identifying ASD in 12-24-month-old children in Tianjin, China. We ascertained the feasibility of training community health practitioners to monitor infants and toddlers for the early signs of ASD, and determined the effectiveness of SACS-C. Furthermore, the SACS-C had a better balance between accuracy and sensitivity in detecting ASD, with the CHAT-23 missing the majority of children on the spectrum (72.7%) vs the SACS-C (46.7%). However, more work is needed to improve the psychometric properties in using the SACS-C in mainland China to make it comparable to its use in Australia.